(untitled) (Texas Journal of Medical Science, 2023)
The results of a comparative study of two groups of children with sepsis who received combined rehabilitation therapy during the rehabilitation period, including correction of the intestinal biocenosis, neurometabolic therapy, and immunotherapy with Viferon, and children who received only the immunomodulator T-activin, showed that an integrated approach to rehabilitation was much more effective. In addition, a relatively rapid immunological effect, good tolerability of viferon, a non-invasive route of administration, and the absence of side effects with the described methods of immunorehabilitation allow us to recommend the use of this drug in infants suffering from sepsis.